Jak kritizovat formy života: filosofie Rahel Jaeggi - Vít Hrouda (Reflexe, 2023)
The article focuses on Rahel Jaeggi’s project of a critique of forms of life. Jaeggi seeks to create a new theory of social critique whose object is what Jaeggi calls a form of life: an ensemble of practices within which we always already live our lives and which represent solutions to certain problems. The critical procedure that Jaeggi defends is an immanent one, meaning that social critics, rather than bringing in external standards, should concentrate on contradictions characterizing forms of life themselves. This procedure presupposes a concept of social change, which happens in a rational way and admits progressive development. This concept in turn serves as the highest criterium for a critique of forms of life.